2020
DOI: 10.1002/apj.2426
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of granular mixing in a rotary drum using a generalized interpolation material point method

Abstract: Numerical simulations using a generalized interpolation material point method (GIMP) and material point method were introduced into the studying of granular mixing in a rotary drum. A Drucker–Prager model that has an equal size with a Mohr–Coulomb criterion was adopted to predict the failure behavior of granular matter. Experiments and discrete element method simulations were conducted to validate the models, and GIMP was finally used due to its accuracy and the ability for eliminating the crossing boundary no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…For the implicit calculation scheme a time step of 5 Â 10 À4 is used. Figure 14 presents the results of the simulation at time step t ¼ 0 s and t ¼ 3:5 s in comparison to [79]. It can be observed that the obtained results show less mixing of the two materials.…”
Section: Granular Mixing In a Rotating Drummentioning
confidence: 96%
See 4 more Smart Citations
“…For the implicit calculation scheme a time step of 5 Â 10 À4 is used. Figure 14 presents the results of the simulation at time step t ¼ 0 s and t ¼ 3:5 s in comparison to [79]. It can be observed that the obtained results show less mixing of the two materials.…”
Section: Granular Mixing In a Rotating Drummentioning
confidence: 96%
“…To show the performance of the moving boundaries including the releasing contact algorithm, the example of the rotating drum proposed by Zuo et al [79] is chosen. They compared the experimental data to the simulations obtained using the discrete element method as well as MPM and GIMP.…”
Section: Granular Mixing In a Rotating Drummentioning
confidence: 99%
See 3 more Smart Citations